Planungskultur - auf der Suche nach einem kontemporären Verständnis räumlicher Planung? - Levin-Keitel, Meike; Othengrafen, Frank (Routledge, 2016)
Die beiden Autoren untersuchen in ihrem Beitrag, welchen Mehrwert der Planungskultur-Ansatz für Wissenschaft und Praxis bislang aufweist und was er theoretisch und empirisch leisten kann. Auf der Suche nach einem kontemporären Verständnis räumlicher Planung ziehen sie Rückschlüsse auch auf das disziplinäre (Selbst-)Verständnis räumlicher Planung und deren ethisch-moralische Setzungen.

This article critically examines the recently introduced and hotly debated conceptual approach of planning cultures. While most scientific papers and studies try to focus on the advantages and forces of planning culture as an analytical approach, this article concentrates more generally on the scientific discourse on planning cultures, i.e. with which intentions the concept has evolved, how it differs from other planning theories, and if the concept has achieved the expected results. By analyzing the original idea of the concept and addressing the complex relationships between culture - including the specific socioeconomic patterns and related cultural norms, values, traditions, and attitudes - and spatial planning as an operative instrument of territorial policy, both the potentials and shortcomings of planning culture are presented and discussed. It is evident that planning culture as a concept allows us to place specific developments, planning routines and principles in direct correlation with each other, offering a new and culturally influenced perspective on the analysis of planning practices. At the same time, it also becomes apparent that the concept is still unclear and faces challenges with regard to its adaptation for empirical research. The main reasons for this might be found in the omnipresence of culture, the static focus of planning culture research, and methodological issues preventing the application of the various models for practical research. The article then concludes in how far the analysis of planning cultures is able to contribute to a contemporary understanding of planning practices and routines, and how research on planning cultures can be improved.
Planning culture - in search of a contemporary understanding of spatial planning.
Keywords: Raumplanung; Planungsprozess; Planungstheorie; Bestandsaufnahme; Forschungsstand; Planungskultur; Begriff; Planungsgeschichte; Verwaltungsforschung; Urban governance; Regional Governance